1979
DOI: 10.1149/1.2129229
|View full text |Cite
|
Sign up to set email alerts
|

Electrodissolution Kinetics of Nickel in Concentrated Acidic Chloride Solutions

Abstract: Anodic nickel dissolution in acidic chloride solutions (constant ionic strengths of 1 and 5M) over a wide range of H + and Cl-concentrations has been investigated. Anodic dissolution in low [H+]-chloride solutions is accelerated by both C1-and OH-with Tafel slopes of about 2.303 RT/F. On

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 16 publications
2
15
0
3
Order By: Relevance
“…In particular, nickel detection was achieved by initially forming a metallic nickel deposit on the BDD electrode and then stripping this deposited metallic layer using a DPV in the anodic sweep and studying the Ni(II)/Ni(III) redox system in a 0.6 M NaCl solution at neutral and acidic solution pHs. The anodic response displayed a characteristic peak at markedly anodic potentials, i.e., +1.070 V vs. Ag/AgCl, which was linearly dependent with the nickel-ion concentration within the range of 10-500 M. Investigations carried out on the analytical signal revealed a pH-dependence of the potential which relied on a 0.5 mole of proton per mole of electrons, not attributable to the system Ni(OH) 2 /NiOOH but rather to a transient adsorbed Ni(II) form such as NiClOH, as described elsewhere [22].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In particular, nickel detection was achieved by initially forming a metallic nickel deposit on the BDD electrode and then stripping this deposited metallic layer using a DPV in the anodic sweep and studying the Ni(II)/Ni(III) redox system in a 0.6 M NaCl solution at neutral and acidic solution pHs. The anodic response displayed a characteristic peak at markedly anodic potentials, i.e., +1.070 V vs. Ag/AgCl, which was linearly dependent with the nickel-ion concentration within the range of 10-500 M. Investigations carried out on the analytical signal revealed a pH-dependence of the potential which relied on a 0.5 mole of proton per mole of electrons, not attributable to the system Ni(OH) 2 /NiOOH but rather to a transient adsorbed Ni(II) form such as NiClOH, as described elsewhere [22].…”
Section: Discussionsupporting
confidence: 53%
“…Conversely, the peak potentials determined below pH 9, i.e., 8.0, 6.2, 5.0 and 4.0, were associated with a different trend with a more noble behaviour and a slope of −30 mV pH unit −1 , thus indicating that the electrochemical process between Ni(II) and Ni(III) hydroxides is unlikely to have occurred. It has been reported that the presence of halide and a high proton concentration interfere in the early stage of Ni(OH) 2 formation due to a competitive adsorption mechanism between OH -or H 2 O and halide, hence affecting the growth and the structure of a thin Ni(OH) 2 outer layer [20][21][22][23]. Specifically, it has been proposed that in solutions containing concentrations of H + and Cl -lower than 1 M (as in our particular case), the dissolution of Ni passes from an adsorbed intermediate of Ni(I) constituted of both Cl -and OH − , i.e., NiClOH -(ads) , which undergoes further oxidation to NiClOH, Ni(II), and hydrolysis reactions [22], as shown in Eqs.…”
Section: Influence Of the Ph On Ni(ii)/ni(iii) Behaviour In Chloride mentioning
confidence: 99%
See 1 more Smart Citation
“…Sauf pour le zinc qui prCsente des oscillations en milieu alcalin, tous les autres exernples ont Ctt dCcrits en milieu acide (1, [3][4][5]. D'autres Ctudes dans les acides chlorhydrique et sulfurique ne citent pas de telles oscillations mais soulignent le r61e des ions chlorure dans l'accC1Cration du processus de corrosion (6)(7)(8)(9). Un cornportement identique a ett signal6 dans des melanges methanol -acide chlorhydrique (10) ou en milieu neutre (I 1).…”
unclassified
“…T y, particularmente CI'(Burstein y Wright, 1976;Bengali y Nobe, 1979;Saraby-Reintjes, 1985). La mayoría de estos autores concluye básicamente que el mecanismo de electrodisolución, similarmente a lo que ocurre con otros metales como Fe y Co, involucra un intermediario adsorbido sobre la superficie del electrodo(Arvia y Posadas, 1975;Real et.…”
unclassified